(untitled) (Research, Society and Development, 2024)
Peripheral neuropathy and diabetic foot syndrome are serious complications of diabetes due to chronic elevation of glucose, resulting in loss of sensation in the feet and risk of ulcers and amputations. Effective prevention includes strict glycemic control, accessible health education and early interventions in primary care, with an emphasis on the multidisciplinary approach as a key strategy for improving patients’ clinical management and quality of life. The aim of this study was to carry out an integrative literature review on the subject of multidisciplinary approaches in the assessment and prevention of diabetic foot. The PICo (Population, Phenomenon and Context) strategy was used to formulate the research question. Studies were selected from electronic databases such as Google Scholar, LILACS and PubMed, prioritizing articles in Portuguese published between 2020 and 2024. The multidisciplinary approach not only optimizes the use of medication, but also promotes crucial behavioral changes, such as adopting a healthy diet and regular physical activity, which are essential for controlling diabetes and preventing foot ulcers. Gaps in clinical practice, especially in the assessment of the diabetic foot in primary health care units, jeopardize the prevention of serious complications. It is recommended to continue comparative studies to strengthen the multidisciplinary model, with the aim of improving health outcomes and reducing costs in the treatment of the diabetic foot, for integrated and continuous care.